Immunotherapy for Medulloblastoma: Current Perspectives - Kabir, Tanvir F (Immunotargets Ther, 2020)
BACKGROUND: Immune-mediated therapies have transformed the treatment of metastatic melanoma and renal, bladder, and both small and non-small cell lung carcinomas. However, immunotherapy is yet to demonstrate dramatic results in brain tumors like medulloblastoma for a variety of reasons. Recent pre-clinical and early phase human trials provide encouraging results that may overcome the challenges of central nervous system (CNS) tumors, which include the intrinsic immunosuppressive properties of these cancers, a lack of antigen targets, antigenic variability, and the immune-restrictive site of the CNS. These studies highlight the growing potential of immunotherapy to treat patients with medulloblastoma, a disease that is a frequent cause of morbidity and mortality to children and young adults. METHODS: We conducted an inclusive review of the PubMed-indexed literature and studies listed in clinicaltrials.gov using combinations of the keywords medulloblastoma, immunotherapy, CNS tumors, brain tumors, vaccines, oncolytic virus, natural killer, and CAR T to identify trials evaluating immunotherapy in preclinical experiments or in patients with medulloblastoma. Given a limited number of investigations using immunotherapy to treat patients with medulloblastoma, 24 studies were selected for final analysis and manuscript citation. RESULTS: This review presents results from pre-clinical studies in medulloblastoma cell lines, animal models, and the limited trials involving human patients. CONCLUSION: From our review, we suggest that cancer vaccines, oncolytic viral therapy, natural killer cells, and CAR T therapy hold promise against the innate immunosuppressive properties of medulloblastoma in order to prolong survival. There is an unmet need for immunotherapy regimens that target overexpressed antigens in medulloblastoma tumors. We advocate for more combination treatment clinical trials using conventional surgical and radiochemotherapy approaches in the near-term clinical development.